A new approach to cultural scripts of trauma sequelae assessment: The sample case of Switzerland. - Rahel Bachem; Amelie Mazza; David J Eberle; Andreas Maercker (PLoS ONE)
Background The novel concept of cultural scripts of trauma sequelae captures culture-specific expressions of posttraumatic distress (e.g., cognitive, emotional, interpersonal, psychosomatic changes) and their temporal associations. Cultural scripts of trauma sequelae complement pan-cultural (etic) diagnoses, such as posttraumatic stress disorder (PTSD) and Complex PTSD, as well as the cultural syndromes concept. Objective This study aimed to develop the cultural scripts of trauma inventory (CSTI) for German-speaking Switzerland and to explore temporal associations of script elements. Method Five semi-structured focus groups were conducted with psychotraumatologists (n = 8) and Swiss trauma survivors (n = 7). The interview schedule included open questions about different domains of potential posttraumatic changes (emotions, cognitions, worldviews, interpersonal relationships, body-related experiences, behavior, and growth). Data were analyzed using qualitative content analysis. Results The Swiss CSTI includes 57 emic elements that represent salient trauma sequelae (30 conformed with a theoretically derived item pool, 27 were newly phrased). Temporal script associations were visualized in a network, whereby self-deprecation, the urge to function and overcompensate, and the urge to hide and endure suffering had the highest number of connections. Conclusion While many posttraumatic changes identified in the present work seem to mirror pan-cultural phenomena represented in the Complex PTSD concept (e.g., self-deprecation), others (e.g., urge to function and perform, urge to hide and endure suffering) may be prominently related to Swiss culture with its value orientations. Knowledge about cultural scripts of trauma sequelae may provide a culture-specific framework that can help to understand individual experiences of distress and enable mental health practitioners to administer culturally sensitive interventions. Pending further validation, the Swiss CSTI bears the potential to advance culture-sensitive assessment of trauma sequelae.